Touch : Attachment and the Body. - White, Kate (Karnac Books, 2004)
Drawn from the Bowlby Memorial Lecture, founded in commemoration of the influential Dr John Bowlby, this volume explores issues of the body and the historically taboo subject of touch in psychoanalysis. It includes contributions from a wide range of professional backgrounds, including two papers presented by pioneering analyst Susie Orbach.